2023
DOI: 10.1017/s1368980023000459
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity is prevalent in a cohort of postpartum women who registered in the Canada Prenatal Nutrition Program in Toronto

Abstract: Objective: To assess the prevalence, severity and socio-demographic predictors of household food insecurity among vulnerable women accessing the Canada Prenatal Nutrition Program (CPNP), and to examine associations between household food insecurity and breastfeeding practices to six months. Design: Cohort investigation pooling data from two studies which administered the 18-item Household Food Security Survey Module at six months postpartum and collected prospective infant feeding data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…As such, a portion of the prenatal period would be captured in most participants’ food insecurity responses. Additionally, a recent Canadian study that collected HFI in the pre and postnatal period found that the HFI status of 80% of participants remained the same over both time periods ( 51 ). Second, although the survey was pre-tested to ensure questions were understandable and acceptable, the survey was self-administered, therefore, participants could not ask for clarity or more detail on survey questions.…”
Section: Discussionmentioning
confidence: 99%
“…As such, a portion of the prenatal period would be captured in most participants’ food insecurity responses. Additionally, a recent Canadian study that collected HFI in the pre and postnatal period found that the HFI status of 80% of participants remained the same over both time periods ( 51 ). Second, although the survey was pre-tested to ensure questions were understandable and acceptable, the survey was self-administered, therefore, participants could not ask for clarity or more detail on survey questions.…”
Section: Discussionmentioning
confidence: 99%